2020
DOI: 10.4252/wjsc.v12.i9.986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of neuropeptide Y on stem cells and its potential applications in orthopaedic disorders

Abstract: Musculoskeletal disorders are the leading causes of disability and result in reduced quality of life. The neuro-osteogenic network is one of the most promising fields in orthopaedic research. Neuropeptide Y (NPY) system has been reported to be involved in the regulations of bone metabolism and homeostasis, which also provide feedback to the central NPY system via NPY receptors. Currently, potential roles of peripheral NPY in bone metabolism remain unclear. Growing evidence suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…2. The NPY gene encodes a neuropeptide expressed throughout the central and peripheral nervous systems [108] and is an essential regulator of bone homeostasis and metabolism [109]. NPY is also a local regulator of osteoblastic lineage and is responsive to mechanical stimuli with potential roles in fracture healing and osteoarthritis [109].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The NPY gene encodes a neuropeptide expressed throughout the central and peripheral nervous systems [108] and is an essential regulator of bone homeostasis and metabolism [109]. NPY is also a local regulator of osteoblastic lineage and is responsive to mechanical stimuli with potential roles in fracture healing and osteoarthritis [109].…”
Section: Discussionmentioning
confidence: 99%
“…The NPY gene encodes a neuropeptide expressed throughout the central and peripheral nervous systems [108] and is an essential regulator of bone homeostasis and metabolism [109]. NPY is also a local regulator of osteoblastic lineage and is responsive to mechanical stimuli with potential roles in fracture healing and osteoarthritis [109]. The WNT10A gene is a member of the WNT gene class and functions within the WNT10A/β-catenin signaling pathway in regulation of adult epithelial proliferation [110,111], mesenchymal stem cell regulation by stimulating osteoblastogenesis [112], coordination of vertebrate segmentation, and motile cilia function [113].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NPY treatment can promote the proliferation of bone marrow stem cells, promote their migration to the lesion area, and participate in the osteogenic differentiation of bone marrow stem cells (16). In addition, NPY and its receptor can regulate the proliferation of HSCs, promote their entry into peripheral blood, and increase the abundance of osteoblasts (16,91,92). Collectively, these studies suggest that NPY can be used in the treatment of osteoporosis with stem cells.…”
Section: Application Of Npy Receptor In the Treatment Of Osteoporosismentioning
confidence: 94%
“…In recent years, the effects of NPY on BMSCs and hematopoietic stem cells (HSCs) have been studied. Studies have shown that NPY treatment can promote the proliferation of bone marrow stem cells, promote their migration to the lesion area, and participate in the osteogenic differentiation of bone marrow stem cells (16). In addition, NPY and its receptor can regulate the proliferation of HSCs, promote their entry into peripheral blood, and increase the abundance of osteoblasts (16,91,92).…”
Section: Application Of Npy Receptor In the Treatment Of Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation